Determining the awareness of surgical nurses regarding frail patients: a cross-sectional study - Öztaş, İsmail and Yava, Ayla and Çelik, Barıış (The European Research Journal, 2024)
Objective: The objective of this study is to determine the knowledge level and awareness of surgical nurses about fragile patients. Method: Obtained through Introductory Information Survey Form created by the researchers and Fragile Patient Information Evaluation Form methods. Results: The average age of the surgical nurses participating in the study was 28±5.01 years, the average professional experience was 5±5.09 years, and the average experience in the service they worked in was 3±2.83 years. The rate of those who heard the term ’frailty’ for the first time is 63%. It was stated that 92.7% of the 110 surgical nurses participating in the study did not receive any training on fragility; It was stated that 50.9% of them think of the most vulnerable and weak patient when they think of a fragile patient. While 50% of them stated that when they suspected frailty in the patient, they evaluated involuntary weight loss, slowness (slowness in walking, muscle weakness), and fatigue; 70% stated that the biggest risk factor for frailty is being depressed or using antidepressant medication. Conclusions: According to the results of the study, it can be said that the awareness of surgical nurses about the "fragile patient" should be increased. In the light of the data obtained, it can be suggested to organize trainings on "fragile patients" for surgical nurses. ’Fragile patient’ education should be included in pre-graduation education and in-service training.